2012
DOI: 10.1159/000337090
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Synaptophysin and Chromogranin A Expression in Patients Receiving Palliative Chemotherapy for Advanced Non-Small-Cell Lung Cancer

Abstract: Background: Chemotherapy is the principal treatment method for patients with advanced non-small-cell lung cancer (NSCLC). Treatment with platinum-based and novel chemotherapeutic regimens, compared to monotherapy, slightly increases the response rates to 20-40%. The predictive and prognostic values of molecular factors are highly variable; however, data on clinical-demographic factors are still burdened by significant limitations. Objectives: The aim of this study was to assess the prognostic value of synaptop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Moreover, the level of IHC markers expression may vary in different histological typing. For instance, expression of Syn was more frequently observed in patients with adenocarcinoma than those with squamous cell carcinoma (12,24). TTF-1 is commonly expressed in poorly differentiated NECs regardless of the site of origin (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the level of IHC markers expression may vary in different histological typing. For instance, expression of Syn was more frequently observed in patients with adenocarcinoma than those with squamous cell carcinoma (12,24). TTF-1 is commonly expressed in poorly differentiated NECs regardless of the site of origin (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Dariusz M.'s study showed that the 12-and 24-month survival rate of patients with Syn expression was 64% in non-small-cell lung cancer, while for patients without expression it was 46% and 16%, respectively. The 12-and 24-month survival rate of patients with CgA expression was 80%, while for CgAnegative patients it was 47% and 19%, respectively (24). Tan D's study showed patients with expression of TTF-1 had a median survival of greater than 57.3 months, while the survival time was only 39.4 months for patients with TTF-1-negative tumors (P=0.006) (35).…”
Section: A B C D E Fmentioning
confidence: 97%
See 1 more Smart Citation
“…However, around the 15th month, mortality in both groups is the same. In groups of positive DLL3 patients with negative chromogranin, the survival rate by the Kaplan-Meier test was slightly higher (p 0.299) [28,29].…”
Section: Outcome Survivalmentioning
confidence: 93%
“…Our data on the expression of chromogranin A corroborate with the studies by Kowalki et al The authors report that chromogranin and synaptophysin are associated with SCLC survival and that they act as an indirect predictive factor. Neoplasms with high rates of chromogranin contain a greater amount of secretory vesicles in neuroendocrine cells, conferring a strong potential for malignant transformation [28,29].…”
Section: Outcome Survivalmentioning
confidence: 99%